A Step towards Patient Safety by Comparing a Trigger Tool with Pre-Existing Tools in the Pharmacovigilance - Palanivel, Malarvizhi; Suresh, Aswini; Palaniappan, Divya Ramasamy; Srinivasan, Dhathri (Indian Journal of Pharmacy Practice)
Aim: To develop a trigger tool for the assessment of Adverse Drug Reaction in hospitalized patients and to compare them with pre-existing tools and validating the new ADR assessment tool. Materials and Methods: A prospective observational study was conducted in tertiary care teaching hospital for a period of six months. 43 patients were selected for the study. The adverse drug reactions were assessed and compared with pre-existing ADR assessment scales with validated SVCP-ADR assessment scale for screening the suspected adverse drug reaction. Results: Total 43 ADRs were reported during the study period, out of which 24 ADR were found in males (56%) and 19 in females (44%). When comparing the SVCP-ADR assessment scale to the five other ADR assessment scales, it showed a higher frequency of positive outcomes (81.39%) compared to the three of those scales. Conclusion: In this study, a tool was created and validated with a content validity index of 0.9 to facilitate the evaluation of Adverse Drug Reactions (ADRs). Furthermore, the results obtained from the five scales such as WHO causality assessment scale, Naranjo Probability scale, Hartwig and Siegel severity scale, Schumock and Thornton scale, Liverpool Avoidability scale were divided into positive and negative outcomes and these outcomes were compared with the SVCP-ADR assessment tool. The study revealed a notable increase in positive outcomes in our tool when compared with the other three scales such as Hartwig and Siegel severity scale, Schumock and Thornton scale, Liverpool Avoidability scale.
Keywords: Pharmacovigilance; Adverse drug reaction; Trigger tool; Validation